1978
DOI: 10.4141/cjps78-151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molybdenum and Lime on the Yield and Molybdenum Concentration of Crops Grown on Acid Sphagnum Peat Soil

Abstract: For personal use only. For personal use only. For personal use only.x : (3,4,5,6,7, 8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…On the contrary, a positive interaction between lime and Mo application in soils on Mo concentration in plants was observed by Gupta (1969). In a later study, Gupta et al (1978) observed that such positive interaction in case of cauliflower was dependent on the level of liming. Synergism between Mo and lime on tissue Mo concentration was observed at low level of lime, while antagonism between them was observed at high levels on dry matter yield.…”
Section: Concentration Of Molybdenum In Plantsmentioning
confidence: 73%
See 1 more Smart Citation
“…On the contrary, a positive interaction between lime and Mo application in soils on Mo concentration in plants was observed by Gupta (1969). In a later study, Gupta et al (1978) observed that such positive interaction in case of cauliflower was dependent on the level of liming. Synergism between Mo and lime on tissue Mo concentration was observed at low level of lime, while antagonism between them was observed at high levels on dry matter yield.…”
Section: Concentration Of Molybdenum In Plantsmentioning
confidence: 73%
“…The effect of Mo was more in S,, while that of lime and P were greater in S 2 soil, the reasons for which have already been mentioned. Gupta et al (1978) and Sharma and Minhas (1992) also observed in greenhouse experiments a significant increase in Mo concentration in cauliflower due to the application of lime in acidic soils. Basak et al (1982) observed a significant increase in the concentration of Mo in rice {Oryza sativa L.) shoot due to P application in soil.…”
Section: Concentration Of Molybdenum In Plantsmentioning
confidence: 83%
“…Legumes like screw bean mesquite have more molybdenum in their roots than other plants. Most plants are not sensitive to excess molybdenum (Gupta, Chipman, and MacKay, 1978). …”
Section: Resultsmentioning
confidence: 99%
“…Nesses trabalhos, as culturas respondem significativamente à aplicação dos nutrientes, a exemplo do N em couve-flor (cv. Júlia) (Pizetta et al, 2005), ao Mo para couve-flor (Gupta et al, 1978). …”
unclassified